Oxidative Stress and Nanotechnology Methods and Protocols - Armstrong, Donald; Bharali, Dhruba J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The emergence of nanotechnology has had a profound effect on almost every aspect of the 21st century’s daily life. It has had a revolutionary impact from stain-resistant clothing and cosmetics to environmental issues , including energy and medicine and even aerospace engineering.  In Oxidative Stress and Nanotechnology: Methods and Protocols, expert researchers in the field detail various aspects of nanotechnology from the oxidative stress point of view. Focusing on synthesis of different antioxidant nanoparticles and antioxidant-loaded nanoparticles, as well as their in vitro/ in vivo mechanisms of action along with their clinical relevance. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Oxidative Stress and Nanotechnology: Methods and Protocols seeks to aid scientists in the further study of techniques for nanotechnology in pathophysiology and protection from the oxidative stress point of view.
Nanoscale Biosensor for Detection of Reactive Oxygen Species -- Nanoparticles: Toxicity, Radicals, Electron Transfer and Antioxidants -- Encapsulation of Anti-Oxidants in Gastrointestinal Resistant Nanoparticulate Carriers -- Toxicity of Novel Nanosized Formulations Used in Medicine -- Fullerenol Nanoparticles: Toxicity and Antioxidant Activity -- Hydrogen Peroxide (H2O2) Detection with Nanoprobes for Biological Applications: A Mini-Review -- Studying the Oxidative Stress Paradigm in vitro: A theoretical and Practical Perspective -- Evaluation of the Effect of Acute and Sub-acute Exposure to TiO2 Nanoparticles on Oxidative Stress -- Biomedical Applications of Nano-antioxidant -- Lipid Peroxidation Due to In Vitro and In Vivo Exposure of Biological Samples to Nanoparticles -- Testing Nanomaterial Toxicity in Unicellular Eukaryotic Algae and Fish Cell Lines -- Gold Nanoparticles and Oxidative Stress in the Blue Mussel, Mytilus edulis -- Oxidative Biomarkers to Assess the Nanoparticles Induced Oxidative Stress -- Vesicular Antioxidants: Role in Age-related Cerebral Oxidative Injury -- Methods for Detection of Oxidative Stress and Genotoxicity of Engineered Nanoparticles -- Size Dependent Study of Pulmonary Responses to Nano-sized Iron and Copper Oxide Nanoparticles -- In vitro Techniques to Investigate the Oxidative Effects of Quantum Dots -- Hybrid Polymeric Nanoparticles: Potential Candidate for Ophthalmic Delivery -- Relevance of Nanotechnology in Modulating Oxidative Stress:  An Overview.
Keywords: Biotechnology; Nanotechnology; Biotechnology; Nanotechnology